Synthesis, Characterization, Chelating Properties and Anti-Fungal Activity of 2-(4-Phenylpiperazinyl) Methyl-3-(8-Quinolinol-5-YL)- 4(3H)-Quinazolinone - C. D. Shelat; R. T. Vashi (E-Journal of Chemistry)
A new quinazolinone derivative namely 2-(4-phenylpiperazinyl)methyl-3-(8-quinolinol-5-yl)- 4(3h)-quinazolinone(HL) was prepared and characterized. Various transition metal (Cu2+, Co2+, Ni2+, Zn2+, Mn2+) chelates of HL were prepared and characterized by metal ligand (M:L) ratio, IR and reflectance spectral studies, magnetic moment, and antimicrobial activity.